SELF-REFLEXIVE MODE OF NARRATIVE: AN ANALYSIS OF BAMA’S KARUKKU - Kaur, Dr. Komalpreet (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For the Dalit women in our patriarchal and caste-based society, Karukku is a vital novel. The protagonist goes through a series of patriarchal or conventional tribulations the entire time. This type of hardship frequently causes women to fall into the lower echelons of society. Whenever Dalit women travel, they are surrounded by a variety of conditions that have been shaped by their caste. With regard to family life, the women adhere to patriarchal rules. With so many social and patriarchal constraints, they are unable to express themselves freely. They end up being labelled as "other" as a result of this. This essay by Bama depicts the tragic situation of Dalit women. She delves into her own personal history of oppression as it pertains to patriarchy and Dalit culture.